2019
DOI: 10.1108/f-07-2018-0081
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and universal design aspects in heritage building refurbishment

Abstract: Purpose The purpose of the paper is to provide a comprehensive overview of the refurbishment of heritage buildings with special emphasis on sustainability and universal design. Findings of the study are the basis for further research and development of enhanced strategies for retrofitting and adaptive reuse of heritage buildings in the framework of sustainability and universal design. Design/methodology/approach The present research focusses on literature review analysis of specific elements of the refurbish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 82 publications
(128 reference statements)
0
22
0
1
Order By: Relevance
“…Factors of cultural and spiritual sphere include establishment on the territory historical and culture traditions and resources, specific for the population values, affirmations, mentality peculiarities. Kristl et al (2019) showed that the current research is related to heritage building renovation and the reuse does not address sustainability and universal design issues comprehensively. They stated that the problem is, in particular, that the topics of culture, heritage and sustainability are dealt separately, although there is a strong interconnection between them (Kristl et al, 2019).…”
Section: Theorization Of Main Concepts 21 Social Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Factors of cultural and spiritual sphere include establishment on the territory historical and culture traditions and resources, specific for the population values, affirmations, mentality peculiarities. Kristl et al (2019) showed that the current research is related to heritage building renovation and the reuse does not address sustainability and universal design issues comprehensively. They stated that the problem is, in particular, that the topics of culture, heritage and sustainability are dealt separately, although there is a strong interconnection between them (Kristl et al, 2019).…”
Section: Theorization Of Main Concepts 21 Social Infrastructurementioning
confidence: 99%
“…Kristl et al (2019) showed that the current research is related to heritage building renovation and the reuse does not address sustainability and universal design issues comprehensively. They stated that the problem is, in particular, that the topics of culture, heritage and sustainability are dealt separately, although there is a strong interconnection between them (Kristl et al, 2019). Economic factors are general economic conditions, determining resource provision of the management practice for the development of social infrastructures.…”
Section: Theorization Of Main Concepts 21 Social Infrastructurementioning
confidence: 99%
“…UHFM creates a strong, mutually supportive, and non-exploitative community by improving human performance, public participation, health, and well-being [27,88], coping with the demand of the citizen who wishes to live close to the city center (but with a community atmosphere) [15] and allowing local communities the chance to participate in the co-design process [66] (Table 4).…”
Section: Integrating Values and Vulnerabilitiesmentioning
confidence: 99%
“…Discussion on the regulatory systems indicated that the law and regulation improvement are needed to enable heritage management to have a legal basis and enhanced the promotion and awareness of heritage protection, thus improving urban sustainability accordingly to the three basic pillars of society, environment, and economy [88,90]. In order to achieve a sustainable UHFM, it is argued that improvement of the heritage laws that enabled restorations' financing, supporting private investors, and creating a diverse, vital and innovative economy should be integrated comprehensively [27,88,91]. Integrating economic, educational, health, and cultural activities could potentially be a catalyst for the development of the community, not only to attract tourists [92,93].…”
Section: Integrating Values and Vulnerabilitiesmentioning
confidence: 99%
“…The European Green Deal lays out the European Commission (2019) strategy to implement the United Nation’s 2030 Agenda and sustainable development goals. Parts of this strategy include a “renovation wave” of public and private buildings and the enforcement of the legislation in relation to the energy performance of buildings, as well as examining initiatives that combine societal pull and technology push in local communities to work towards a sustainable future (Kristl et al , 2019). This paper argues that ambition of cities to prepare for the future by means of smart sustainable technology and efficient use of resources in the continued urbanization first and foremost requires enhanced citizen participation.…”
Section: Introductionmentioning
confidence: 99%